Assessing future impacts of tropical cyclones on global banana production - S. Kaashoek; Ž. Malek; Ž. Malek; N. Bloemendaal; N. Bloemendaal; M. C. de Ruiter (Natural Hazards and Earth System Sciences)
Tropical cyclones (TCs) are projected to increase in intensity globally, impacting human lives; infrastructure; and important agricultural activities, such as banana production. Banana production is already impacted by TCs in several parts of the world, leading to price volatility and impacted livelihoods of banana producers. While many potential impacts on banana production have already been quantified on a local scale, it remains unclear how bananas could be impacted by TCs across the globe under present and future climate conditions. To address this, we first looked at the documented impacts of TCs on banana production from different places all around the world. Using spatially explicit data on banana-producing regions and future TC occurrence and magnitude, we then identified the spatial distribution and extent of areas where TCs could impact banana production. Our results suggest that considerable portions of global banana production are at risk of being impacted by TCs under present and future climate conditions, and we show this for different return periods.